Gua Sha, a press-stroke treatment of the skin, boosts the immune response to intradermal vaccination - Tingting Chen; Ninghua Liu; Jinxuan Liu; Xiaoying Zhang; Zhen Huang; Yuhui Zang; Jiangning Chen; Lei Dong; Junfeng Zhang; Zhi Ding (PeerJ, 2016)
Objective The skin is an important immunological barrier of the body as well as an optimal route for vaccine administration. Gua Sha, which involves press-stroke treatment of the skin, is an effective folk therapy, widely accepted in East Asia, for various symptoms; however, the mechanisms underlying its therapeutic effects have not been clarified. We investigated the influence of Gua Sha on the immunological features of the skin. Methods Gua Sha was performed on BALB/c mice and the effects were evaluated using anatomical, histological, and cytometric methods as well as cytokine determination locally and systemically. The effect on intradermal vaccination was assessed with antigen-specific subtype antibody responses. Results Blood vessel expansion, erythrocyte extravasation, and increased ratios of immune active cells were observed in the skin tissue following the treatment. Pro-inflammatory cytokines were up-regulated, and immunosuppressive cytokines, down-regulated, in the treated and untreated skin and systemic circulation; no obvious variations were detected in case of anti-inflammatory cytokines. Interestingly, intradermal delivery of a model vaccine following Gua Sha induced about three-fold higher IgG titers with a more Th1-biased antibody subtype profile. Conclusion Gua Sha treatment can up-regulate the innate and adaptive immune functions of the skin and boost the response against intradermal antigens. Thus, Gua Sha may serve as a safe, inexpensive, and independent physical adjuvant for intradermal vaccination.